Comparison of cellooligosaccharide conformations in complexes with proteins with energy maps for cellobiose. (15th July 2021) - French, Alfred D.; Montgomery, David W.; Prevost, Nicolette T.; Edwards, J. Vincent; Woods, Robert J.
Graphical abstract: Highlights: Linkage torsion angles of cellodextrins in crystalline protein complexes were studied. They were compared with those of cellulose, small molecules, and complexed lactose. They were also compared with quantum mechanics maps for cellobiose and analogs. Predicted amorphous cellulose had extended 2-fold to left-handed 3-fold shapes. Most experimental torsions fit better on the energy map for hydroxyl-less analog. Abstract: Shapes (conformations) of cellulose molecules are described by their glycosidic linkage torsion angles ϕ and ψ. Although the torsions are known for cellulose in crystals, amorphous shapes are also interesting for understanding reactivity and physical properties. ϕ and ψ determination for unorganized matter is difficult; one approach is to study their range in many related molecules. For example, linkage torsions of cellulose should be similar to those in cellobiose. Herein, torsions were measured for cellooligosaccharides and lactose moieties complexed with proteins in the Protein Data Bank (PDB). These torsions were compared with ϕ/ψ maps based on quantum mechanics energies for solvated cellobiose and analogs lacking hydroxyl groups. Most PDB conformations corresponded to low map energies. Amorphous cellulose should be generally extended with individual linkages that would give 2- to 3-fold helices. The map for an analog lacking hydrogen bonding ability was more predictive for PDB linkages than the cellobiose map.